The Representation of Meaning in the UMLS - McCray, A. T.; Nelson, S. J. (Methods of Information in Medicine, 1995)
The UMLS knowledge sources provide detailed information about biomedical naming systems and databases. The Metathesaurus contains biomedical terminology from an increasing number of biomedical thesauri, and the Semantic Network provides a structure that encompasses and unifies the thesauri that are included in the Metathesaurus. This paper addresses some fundamental principles underlying the design and development of the Metathesaurus and Semantic Network. It begins with a description of the formal properties of thesauri, including the Metathesaurus, and the formal properties of the Semantic Network. It continues with consideration of the principle of semantic locality and how this is reflected in the UMLS knowledge sources. The paper concludes with a discussion of the issues involved in attempting to re-use knowledge and the potential for re-use of the UMLS knowledge sources.
Keywords: UMLS; Knowledge Representation